The Influence of Nutrient Intake and Blood-Boosting Tablet Consumption on Anemia among Female Students of Tebing Tinggi Vocational High School - Friska Anita Rismawaty Manurung; Zulhaida Lubis; Etti Sudaryati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Adolescent girls have a tenfold higher risk of developing anemia compared to boys. This is due to factors such as monthly menstruation and increased iron requirements during growth. This study aims to analyze the influence of nutrient intake, vitamin C and the consumption of iron supplements, on anemia among female students at SMKN schools in Kota Tebing Tinggi. The study follows an observational analytic design with a cross-sectional approach. The findings of the study did not show any significant influence the consumption of iron supplements on the anemia status of female students at SMKN schools in Kota Tebing Tinggi. However, there was a significant impact of vitamin C intake on the anemia status of female students. It is recommended that schools raise awareness among female students about the importance of balanced nutrition in preventing anemia through counseling, campaigns, promoting understanding about the consumption of iron supplements, and providing support to maintain consistency in their consumption.